Exploring Sustainable Tourism Resources to Realise Ergo Green Tourism in Indonesia - Andriyansah, Andriyansah; Subchan, Subchan; Pamungkas, Kasno; Geraldina, Ira; Arifin, Andi Harmoko; Manggarani, Cynthia Ayu (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research examines sustainable tourism in Indonesia, focusing on Ergo Green Tourism, a model that integrates ergonomic principles with green tourism. With the tourism sector significant economic contribution, there is a growing need for a model that balances environmental sustainability with tourist comfort. The research aims to evaluate the Ergo Green Tourism model by analyzing the relationships between Environmental Green Knowledge, Green Marketing, and Environmental Protection in promoting sustainability and improving tourism performance in Indonesia. A quantitative approach using Structural Equation Modeling (SEM) was employed. Data was gathered from MSMEs in key Indonesian tourist destinations through structured questionnaires and in-depth interviews, combining both quantitative and qualitative insights. The findings show that environmental protection and environmental knowledge positively influence green marketing, Ergo Green Tourism, and sustainability. Furthermore, green marketing significantly enhances the development of Ergo Green Tourism. This research highlights the importance of integrating green and ergonomic practices into tourism. It provides actionable insights for stakeholders, including MSMEs and policymakers, and suggests further research to refine the model and assess its long-term impact across different regions in Indonesia.